The Effect of Profit Persistency, Business Risk and Capital Structure on Earnings Return Coefficient with Good Corporate Governance as Moderating Variable - Suharti, Suharti; Murwaningsari, Etty (Journal of Applied Business and Technology, 2024)
This research aims to analyze the impact of profit persistence, business risk, and the form of capital on the earning return coefficient. This research attempted to quote inferior information from the Indonesian Stock Exchange for the 2014-2020 period. The population in this research is the industrial zone listed on the Indonesian Stock Exchange throughout the 2016-2020 period. The research population is 56 industries. The sample collection method used was purposive sampling. The research sample consisted of 40 industries. The analysis used in this research uses multiple linear regression using SPSS. The research results prove that profit persistence and business risk have no effect on ERC, on the contrary, DER has an effect on ERC. The GCG variable weakens the relationship between profit persistence and business risk on ERC, but GCG strengthens the influence of DER on ERC.